The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.3945/jn.113.189118
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin D Inadequacy Accelerates Calcification and Osteoblast-Like Cell Formation in the Vascular System of LDL Receptor Knockout and Wild-Type Mice

Abstract: Vitamin D insufficiency is highly associated with cardiovascular morbidity and mortality. We have demonstrated enhanced vascular calcification in LDL receptor knockout (LDLR(-/-)) mice fed a diet low in vitamin D. This study aimed to investigate the impact of a diet low in vitamin D on vascular calcification in wild-type (WT) mice lacking atherosclerotic plaques and the effects of a persistent and discontinuous vitamin D insufficiency on atherosclerotic plaque composition in LDLR(-/-) mice. The study was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…There is evidence from experimental studies that important cardiovascular risk factors such as vascular calcification, foam cell formation and macrophage cholesterol uptake may be suppressed by adequate vitamin D supply [5,6]. Deficient and insufficient vitamin D status, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…There is evidence from experimental studies that important cardiovascular risk factors such as vascular calcification, foam cell formation and macrophage cholesterol uptake may be suppressed by adequate vitamin D supply [5,6]. Deficient and insufficient vitamin D status, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, some micronutrient deficiencies may promote AC via this mechanism. Feeding mice with low vitamin D for 16 wk, Schmidt et al (89) observed more calcified spots in the aortic valve than those given adequate vitamin D, accompanied by higher expressions of BMP2 and Runx2. Similarly, in animal VSMCs calcification models, administration of Mg dose-dependently decreased expressions of BMP2, osteocalcin, and ALP, leading to amelioration of VSMCs calcification (44,70).…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 99%
“…There are no human intake studies with respect to CV calcification, probably because dietary vitamin D provides only a relatively small contribution to serum 25(OH)D. Animal studies, however, show that high vitamin D intake can induce CV calcification and impair endothelial function 128,129 but they also show that a vitamin D deficient diet can induce an increase in calcified lesions [130][131][132] , indicating that both excess and deficiency are detrimental. Several epidemiological studies measuring serum 25(OH)D demonstrate an absence of association with presence or extent of CAC, MAC, cIMT, degree of carotid stenosis or mean arterial pressure 22,[133][134][135] , although patients with calcific aortic stenosis 136 and poor coronary collateral circulation 137 140 and with the calcification score in peripheral arterial disease 27 .…”
Section: Ectopic Calcificationmentioning
confidence: 99%